PENGARUH CAPITAL EXPENDITURE, INVESTMENT OPPORTUNITY SET, PERTUMBUHAN PERUSAHAAN, DAN STRUKTUR MODAL TERHADAP DIVIDEND PAYOUT RATIO - Lilis Daryanti (Ma Chung Press, 2016)
This purpose of research to determine the effect of four independent variable the capital expenditure, investment opportunity set, capital structure, and growth of the company to dividend payout ratio. This research with the secondary data, a methods of the sampling collection by using the methods purposive sampling, with the criteria of manufacturing companies listed in Indonesia Stock Exchange (BEI) for 6 years, the company paying the dividends and the companies that issue financial statements continuously during the period 2010- 2015. The samples of the based on the criteria that side of 8 companies. Instrument the analysis used is linier regression multiple, and assumption classical is also used in this research that is the normality test. Based on the results of this research it can be seen that variable capital expenditure has not been affecting the dividend payout ratio in property & real estate companies at Indonesia Stock Exchange. Meanwhile, Investment opportunity set, capital structure, and the growth of the company significant positive effect on dividend payout ratio on company property & real estate in the Indonesia Stock Exchange that investors need first to consider the structure of capital and the growth of a company before deciding to invest in company shares.